An Autopsy Based Retrospective Analysis of the Profile of Poisoning Cases at a Tertiary Health Care Centre in Central India Region - Baveja, VS; Patel , NS; Nigam, M; Nigam , K; Agrawal, V; Chouksey , VK; Tomar, JS (Journal of Indian Academy of Forensic Medicine, 2024)
Acute poisoning is a crucial medical emergency and has remained one of the commonest causes of unnatural deaths. The earlier the initial resuscitations, gastric decontamination and use of specific antidotes, the better the outcome. The aim of this study was to characterize the poisoning cases admitted to the tertiary care health centre in Vidisha district. All cases brought for autopsy between the period January 2022 to December 2023 were evaluated retrospectively. We reviewed data obtained from the medical records as well as the data entries made in the pre-structured formats filled at the time of performing autopsy. It was found that 38% of all medico-legal deaths were due to poisoning. Males constituted 71.27% cases. Maximum victims, 31.38% belonged to the 21-30 years age group. 65.95% of the total victims were found to be married. The place of incidence was found to be indoors in 82% cases and history of addiction was provided in 20% cases. About 39% cases were brought alive to the hospital and the survival period in about 55% of the brought alive cases was less than 24 hours. By means of this study, poisoning has been recognised as one of the most common cause of suicidal mortality. Strengthening of peripheral health centres by means of better treatment modalities along with better access for psychological support and regulation on sale of agricultural poisons can help in curbing the mortality caused as a result of poisoning.